2002
DOI: 10.1042/cs103s272s
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelin-1 in the development of a special type of cardiomyopathy

Abstract: The role of endothelin-1 (ET-1) in certain pathological states is still unclear. We have investigated the effect of anthracyclines (maximum dose, 450 mg/m(2) of body surface) on left ventricular systolic and diastolic function and how it influences the level of plasma ET-1 in 21 patients (12 female and nine male) with Hodgkin and non-Hodgkin lymphoma. We also studied the association between plasma ET-1 concentration and echocardiographic parameters. Serum ET-1 was measured by ELISA. Left ventricular function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Endothelin‐1 (ET‐1) is among a number of biomarkers that have been postulated to play a role in predicting the development of cardiomyopathy associated with CPA. In some small studies, a decrease in ET‐1 levels has been shown to correlate well with a decrease in EF after anthracycline administration 10 . This suggests that the reduction in ET‐1 is a result of the direct cytotoxic effect of anthracyclines.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Endothelin‐1 (ET‐1) is among a number of biomarkers that have been postulated to play a role in predicting the development of cardiomyopathy associated with CPA. In some small studies, a decrease in ET‐1 levels has been shown to correlate well with a decrease in EF after anthracycline administration 10 . This suggests that the reduction in ET‐1 is a result of the direct cytotoxic effect of anthracyclines.…”
Section: Discussionmentioning
confidence: 96%
“…In some small studies, a decrease in ET-1 levels has been shown to correlate well with a decrease in EF after anthracycline administration. 10 This suggests that the reduction in ET-1 is a result of the direct cytotoxic effect of anthracyclines. If this is indeed the case, CPA may play a similar role in reducing ET-1 levels.…”
Section: Discussionmentioning
confidence: 99%